Technické opatření pro zajištění informační bezpečnosti na podnikatelské fakultě - Kajan, Tomáš (Vysoké učení technické v Brně. Fakulta podnikatelská, 2022)
Diplomová práca sa zameriava na návrh technických opatrení slúžiacich na docielenie informačnej bezpečnosti na Fakulte podnikateľskej, ktorá je súčasťou univerzity Vysoké učení technické v Brne. Návrh sa vo veľkej miere riadi Vyhláškou o kybernetickej bezpečnosti, ktorú dopĺňa rada noriem ISO/IEC 27000. Výstupom práce sú technické opatrenia, ktoré doprevádzajú smernice na vybrané časti opatrení.

The diploma thesis focuses on the design of technical measures used to achieve information security at the Faculty of Business and Management, which is part of the Brno University of Technology. The proposal is largely governed by the Cyber Security Ordinance, which is complemented by a series of ISO/IEC 27000 standards. The output of the work is technical measures that accompany the directives on selected parts of the measures.
Technical security measures to ensure information security at Faculty of business and management
Keywords: kybernetická bezpečnosť; ISO/IEC 27000; VKB; zraniteľnosti; technické opatrenia; VUT FP; cyber security; ISO/IEC 27000; VKB; vulnerabilities; technical measures; BUT FBM